Biofabrication of endothelial cell, dermal fibroblast, and multilayered keratinocyte layers for skin tissue engineering. (9th April 2021) - Barros, Natan R; Kim, Han-Jun; Gouidie, Marcus J; Lee, KangJu; Bandaru, Praveen; Banton, Ethan A; Sarikhani, Einollah; Sun, Wujin; Zhang, Shiming; Cho, Hyun-Jong; Hartel, Martin C; Ostrovidov, Serge; et al.
Abstract: The skin serves a substantial number of physiological purposes and is exposed to numerous biological and chemical agents owing to its large surface area and accessibility. Yet, current skin models are limited in emulating the multifaceted functions of skin tissues due to a lack of effort on the optimization of biomaterials and techniques at different skin layers for building skin frameworks. Here, we use biomaterial-based approaches and bioengineered techniques to develop a 3D skin model with layers of endothelial cell networks, dermal fibroblasts, and multilayered keratinocytes. Analysis of mechanical properties of gelatin methacryloyl (GelMA)-based bioinks mixed with different portions of alginate revealed bioprinted endothelium could be better modeled to optimize endothelial cell viability with a mixture of 7.5% GelMA and 2% alginate. Matrix stiffness plays a crucial role in modulating produced levels of Pro-Collagen I alpha-1 and matrix metalloproteinase-1 in human dermal fibroblasts and affecting their viability, proliferation, and spreading. Moreover, seeding human keratinocytes with gelatin-coating multiple times proved to be helpful in reducing culture time to create multiple layers of keratinocytes while maintaining their viability. The ability to fabricate selected biomaterials for each layer of skin tissues has implications in the biofabrication of skin systems for regenerative medicine and disease modeling.